2017
DOI: 10.2351/1.4983269
|View full text |Cite
|
Sign up to set email alerts
|

Application of high speed filming techniques to the study of rearwards melt ejection in laser drilling

Abstract: Melt ejection is the dominant material removal mechanism in long, ms, pulse laser drilling of metals, a process with applications such as the drilling of cooling holes in turbine blades. Droplets of molten material are ejected through the entrance hole and, after breakthrough, through the exit hole. High speed filming is used to study the ejected material in order to better understand how this debris may interact with material in the immediate vicinity of the drilled hole. Existing studies have quantified vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Using the raw pixel intensity values, the melt pool is observed during processing and a qualitative assessment of the amount of spatter ejected during melting is made. Image processing and analysis was carried out on the intensity images using particle segmentation methods developed in [22]. The images were segmented using Otsu's method [23] combined with a Watershed Transform Function in order to distinguish spatter particles.…”
Section: High-speed Melt Pool Monitoringmentioning
confidence: 99%
“…Using the raw pixel intensity values, the melt pool is observed during processing and a qualitative assessment of the amount of spatter ejected during melting is made. Image processing and analysis was carried out on the intensity images using particle segmentation methods developed in [22]. The images were segmented using Otsu's method [23] combined with a Watershed Transform Function in order to distinguish spatter particles.…”
Section: High-speed Melt Pool Monitoringmentioning
confidence: 99%
“…By reviewing the conducted researches in the field of MFUV-Aided LD, 127 it has been found that limited studies have been performed on evaluating the effect of simultaneous application of magnetic field and ultrasonic vibration on the microstructure of the machined part. Therefore, in this paper, the simultaneous application of magnetic field (with various intensities) and ultrasonic vibrations (with different amplitudes) were studied on the formed phases, thickness of recast layer and thickness of HAZ in the LD of Ti6Al4V.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, laser drilling (LD) has found a special place in various industries, including drilling parts in aerospace devices and cooling holes for turbine blades [1][2][3][4] as well as drilling parts of medical devices such as implants. 5 Despite the widespread applications, this process has encountered several restrictions such as low penetration depth, high thickness of recast layer, high thickness of HAZ, micro-cracks and spattering.…”
Section: Introductionmentioning
confidence: 99%